Primary intradural intramedular spinal melanocytoma - Almagro Allende, Stefania Esther; Berra, Matías; Sánchez, Javier; Farah, Zamira (Revista Argentina de Neurocirugía, 2025)
Background: meningeal melanocytoma is a benign tumor originating from leptomeningeal melanocytes derived from the neural crest. Its incidence is less than 1%. Its most common location is the posterior fossa and, to a lesser extent, the spinal cord, where it tends to behave extramedullary. Intramedullary presentation is very rare. It is characterized by slow growth and a risk of local recurrence and malignant transformation. The main therapeutic option is surgery, with the best results following total excision. Objectives: to report a case of primary intradural spinal melanocytoma and analyze the literature on the subject. Case description: a 54-year-old patient with a cervical MRI consistent with an intradural space-occupying lesion extending from C3 to C7, measuring 12.2 mm x 9.7 mm x 20.7 mm, with a mass effect on the spinal cord tissue, hyperintense on T1 and T2 weights, and with uptake after contrast injection. Surgery: a posterior cervical approach was used to perform laminoplasty from C3 to T1, longitudinal dural opening, and longitudinal dorsal myelotomy from C3 to T1, with evidence of the aforementioned brown intramedullary lesion; the lesion was resected using intraoperative monitoring. Conclusion: surgery should be considered the treatment of choice, even in partial resection settings, where radiotherapy may be a useful complementary therapeutic tool.